Injury risk is greater in physically mature versus biologically younger male soccer players from academies in different countries. (May 2022) - Hall, Elliott C.R.; Larruskain, Jon; Gil, Susana M.; Lekue, Josean A.; Baumert, Philipp; Rienzi, Edgardo; Moreno, Sacha; Tannure, Marcio; Murtagh, Conall F.; Ade, Jack D.; Squires, Paul; Orme, Patrick; et al.
Abstract: Objectives: To investigate if maturity status was associated with injury risk in male academy soccer players. Design: Prospective cohort surveillance study. Setting: Professional soccer academies. Participants: 501 players (aged 9–23 years) from eight academies in England, Spain, Uruguay and Brazil. Main outcome measures: Players were grouped by maturity offset as pre-peak height velocity (PHV), circa-PHV, post-PHV or adult. Injury prevalence proportion (IPP) and days missed were recorded for one season per player, with training/match exposure recorded in a sub-sample (n = 166). Results: IPP for all injuries combined increased with advancing maturity, with circa-PHV (p = 0.032), post-PHV (p < 0.001) and adult (p < 0.001) higher than pre-PHV. IPP was higher in post-PHV and adult than pre-PHV for non-contact (p = 0.001 and p = 0.012), soft-tissue (both p < 0.001), non-contact soft-tissue (p < 0.001 and p = 0.005), muscle (both p < 0.001), thigh (both p < 0.001), ankle (p = 0.035 and p = 0.007) and hamstring injuries (p = 0.041 and p = 0.017). Ligament/tendon IPP was greater in adult versus pre-PHV (p = 0.002). IPP for growth-related injuries was lower in post-PHV than pre-PHV (p = 0.039). Injury incidence rates (n = 166) exhibited similar patterns to IPP in the full cohort. Conclusions: Injury patterns were similar between post-PHV and adult academy players but, crucially, relatively more of these groups suffered injuries compared to pre- and circa-PHV (except growth-related injuries). Highlights: Injury prevalence proportion (IPP) was recorded in 501 academy soccer players. IPP was higher in post-peak height velocity (PHV) vs. pre- and circa-PHV players. Injury incidence rates in a sub-sample of players exhibited a similar pattern to IPP. IPP was generally higher in Spain but lower in Uruguay and Brazil vs. England. However, IPP increased with advancing maturity status across countries.